Smart Calculator 4.0 / Yusrina Andu ... [et al.]. - Andu, Yusrina; Mohamed, Nadiah; Othman, Norlida; Ismail, Norul Fadhilah; Ahmad, Siti Noor Dina (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Smart Calculator 4.0 program is designed to support the pre-diploma and diploma students to get the most out of their calculator to solve mathematics and statistics questions. This program aims to narrow the gap between manual calculation methods and modern technological tools as well as provide support to students in improving their accuracy, efficiency and problem-solving skills. Through this program, these students can increase their experience, knowledge and understanding on the practical usage of their calculators to the fullest. Precision and efficiency are important in problem-solving. For students who find solving mathematics as challenging, the ability to use calculator efficiently is essential. As digitalization and educational advance further, mastering smart tools such as calculators can significantly increase the ability of problem-solving among students. Although manual calculations still present, nonetheless the adaptation of calculator in speeding the calculation time for mathematics problem cannot be neglected. Besides that, using calculator smartly can reduce student error especially when solving complex calculations. This would benefit students who may struggle with accuracy when calculating manually. Therefore, these advantages presented here shows that it is highly essential to empower students with these calculator skills. Thus, Smart Calculator 4.0, the fourth instalment of using calculator was held from 13th May 2024 until 17th of May 2024 during mathematics class and the participants are from Pre-Diploma and Diploma students from UiTM Cawangan Negeri Sembilan, Kampus Kuala Pilah.